FINITE ELEMENT MODELING OF CIRCULAR REINFORCED CONCRETE COLUMN CONFINED WITH CFRP UNDER ECCENTRIC LOADING - Angga Bayu Christianto; Bambang Piscesa; Faimun Faimun; Pujo Aji (Institut Teknologi Sepuluh Nopember (ITS), 2019)
This paper presents nonlinear finite element analysis of eccentrically loaded circular Reinforced Concrete (RC)column confined with Carbon Fiber Reinforced Polymer (CFRP) wraps. The concrete constitutive model uses a plasticityfracture model which is restraint sensitive, utilize a non-constant plastic dilation rate, and is able to simulate the plasticvolumetric compaction of concrete core under high confining pressure. For validation of the models, two available specimensfrom the literature are used in the validations. Excellent agreement between the numerical models and the available test resultsare obtained in this study. A detailed investigation on the confinement effectiveness of both external and internal confiningdevices are presented and discussed. This discussion of the confinement effectiveness is important to be included in the designformula.